Extra- and intracellular gold nanoparticles synthesis using live peanut callus cells - Raju, D.; Mehta, Urmil J.; Ahmad, Absar (Current Nanoscience, 2013)
An important challenge of considerable topical significance in nanotechnology is the development of eco-friendly experimental processes for the synthesis of nanomaterials in large quantities with variable sizes, shapes and chemical compositions. Green synthesis routes for the production of inorganic metal nanoparticles using whole cell of microorganisms and plant extracts are gaining tremendous popularity as these are non-toxic, cheap and occur at ambient conditions. The present work emphasizes on gold nanoparticles synthesis protocol using live plant callus cells. Peanut callus cells when incubated with HAuCl4 solution in ambient conditions reduced the precursor and lead to formation of well dispersed, water soluble extracellular and intracellular gold nanoparticles within 24 hours. The biosynthesis of gold nanoparticles was monitored by UV-visible spectroscopy (UV-Vis) and further characterized by X-ray diffraction analysis (XRD), Energy Dispersive Spectroscopy (EDS) and Selected Area Electron Diffraction (SAED). The particle size distribution shows that the average particle size is 50 nm for extra-and 31 nm for intracellular gold nanoparticles. The nanoparticles may be stabilized by proteins secreted by callus cells. The reduction process is believed to occur enzymatically, thus creating the possibility of a rational, plant cell-based method for the synthesis of nanoparticles over a wide range of chemical compositions.
Keywords: Biosynthesis; callus; gold nanoparticles; live cells; Peanut; TEM

Extracellular synthesis of silver nanoparticles using living peanut seedling - Raju, D.; Paneliya, Nikita; Mehta, Urmil J. (Applied Nanoscience, 2014)
Synthesis of nanoparticles by environment friendly method is an important aspect of nanotechnology. In the present study, extracellular reduction of silver ions to silver nanoparticles was carried out using living peanut plant. The electron microscopic analysis shows that the formed nanoparticles were of different shapes and sizes. The formed nanoparticles were polydispersed. The shapes of the nanoparticles were spherical, square, triangle, hexagonal and rod. Most of the particles were spherical and 56 nm in size. EDS analysis confirmed the formed nanoparticles were of silver. The crystalline nature of nanoparticles was confirmed by diffraction. This method opens up an exciting possibility of plant-based synthesis of other inorganic nanomaterials. This study confirms the synthesis of extracellular silver nanoparticles by living plant.
Keywords: Nanoparticles; Shapes; Silver; synthesis; TEM